A framework for assessing perceived trust and security in electronic payments system : A case study of Iraq - Thiab, Ali Shawket (2019)
E-commerce is based on electronic payment systems (EPS) and the growing volume of e-commerce makes EPS more important for both businesses and consumers. The usage of EPS in Iraq is suffering from many difficulties and problems in implementation and consistency although it is considered to be in its main phases of development. Among the problems are about the users’ perceived security and trust. Perceived security can be defined as a subjective evaluation of the security of the EPS by the consumer, while perceived trust referred to the belief of consumers that e-payment transactions will be processed according to their expectations. The lack of perceived security and trust has been identified as one of the most vital factors slowing the development of e-commerce. This poses a challenge to the Iraq government in realizing the initiatives of e-services particularly in the EPS initial phase, identification phase, build phase, integration phase, fine tune and expansion phase. However, there has been lack of study to advance the understanding in the subject of citizens’ perceived trust and security that affecting the EPS usage in Iraq. This research addresses this gap through an empirical study of perceived trust and security factors in impacting EPS usage in Iraq. In this research a framework is designed to describe the determinant factors of perceived trust and security, its relationship, and the subsequent effect on the EPS use. In order to understand the level of trust in Iraq, a survey was conducted among citizen of Iraqi with different academic levels in regard to trust and security factors. The determinant factors are obtained based on previous research theories, which are: transaction procedure, technical protection, perceived privacy, perceived security, perceived usefulness, and perceived ease of use of EPS. A sample of 422 respondents was analysed through structural equation modelling (SEM); the findings indicate that both perceived trust and security factors have a significant influence on EPS use. The effect of perceived trust on the use of EPS, emphasized as a regression coefficient in the results, has been found to be a strong one. This research contributes to the area of trust and security perception in e-commerce with particular interest on Iraq. The results of this study will be a point-out of the basics framework of trust and security perceptions for electronic payment systems in Iraq. The findings will help the current implementation challenges; in order to conform to the electronic payment systems requirements towards establishments of e-services in Iraq.